Thermal performance and experimental analysis of stainless steel flat plate solar collector with full-flow channels - Yi He; Hongwen Yu; Guangbin Duan; Yong Wang; Qianfu Yang; Lei Feng; Jiaming Zhang (Heliyon, 2024)
The thermal performance of a flat plate solar collector (FPSC) is a critical indicator that depends on the environment, operational parameters, and dimensions. This study examines the impact of size on thermal performance improvement mechanisms. Firstly, numerical simulation models are introduced as the foundation for optimization research. This involves analyzing the flow resistance of microchannels and defining their structural parameters. Furthermore, experimental tests were conducted on a stainless steel flat plate solar collector (S/S FPSC) with the best design parameters to validate the accuracy of the mathematical model during the design phase. The results indicate that increasing the width of the microchannel and the height of corrugations can effectively enhance the thermal performance of the S/S FPSC. The momentary efficiency is projected to reach a remarkable 86.10% under ideal circumstances. Additionally, a mathematical expression was proposed to establish the relationship between the surrounding conditions and the momentary efficiency of the S/S FPSC. Moreover, the microchannel comprises S/S material, maintaining a homogeneous temperature distribution to maximize heat absorption. The use of stainless steel also extends the lifespan of the FPSC.